Self-Regulated Learning as a Predictor of Learning Achievement of Underachiever Students at SMPN 12 Bekasi City - Rosidah, Rosidah; Sri Pertiwi, Eva (International Journal of Social Science, Education, Communication and Economics, 2024)
This study explores the impact of self-regulated learning on the academic achievement of underachieving students at SMPN 12 Bekasi City. Self-regulated learning, a critical element in academic success, includes the ability to plan, monitor, and evaluate one’s learning activities. The research employed a quantitative descriptive method, selecting 49 underachieving students through purposive sampling. Data collection was conducted using structured questionnaires completed by the students. Statistical analysis identified a significant but negative relationship between self-regulated learning and academic performance, with a correlation coefficient of -0.172. This suggests that students with lower self-regulation tend to perform worse academically. The findings highlight the importance of targeted interventions to improve self-regulated learning skills among underachievers, which could potentially enhance their academic success.